Development of microzonation maps of Kuala Lumpur city centre for seismic design of buildings - Azlan, Adnan, Assoc. Prof.; Henrriyawan, Prof.; Aminaton Marto (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/